Genesis of diamonds and associated phases - Litvin, Yuriy A. (Springer, 2017)
This book presents an overview of recent advances in our understanding of the genesis of diamonds and the associated phases. It is divided into three main parts, starting with an introduction to the analysis of diamond inclusions to infer the formation processes. In turn, the second part of the book presents high-pressure experimental studies in mantle diamond-parental mineral systems with representative multicomponent boundary compositions. The experimental syngenesis phase diagrams provided reveal the physicochemical mechanisms of diamond nucleation and substantiate the mantle-carbonatite concept of the genesis of diamonds and associated phases. Lastly, the book describes the genetic classification of diamond-hosted mineral inclusions and experimentally determined RE "mineral-parental melt" partition coefficients. The physicochemical experimental evidence presented shows the driving forces behind the fractional evolution of the mantle magmas and diamond-parental melts. Given the depth and breadth of its coverage, the book offers researchers essential new insights into the ways diamonds and associated minerals and rocks are naturally created.
Keywords: Diamonds.; elektronické knihy; electronic books